Primary crime-related outcome indicators associated with recreational cannabis legalization: a comprehensive literature and data review - Fischer, Benedikt (Crime, law and social change, 2024)
Cannabis policies are increasingly being liberalized, including the implementation of formal legalization policies of non-medical use and supply in multiple jurisdictions (initially in the Americas) towards improved public health and safety objectives. While focus on health indicators has shown mixed or adverse outcomes, less attention has been given to social-legal – and specifically crime-related – outcomes of legalization. We conducted a comprehensive literature and data review of key crime-related outcomes associated with non-medical cannabis legalization in four main domains, based on targeted searches of recent academic (e.g., journal publication) and ‘grey’ English-language literature sources: 1) cannabis-related crimes and enforcement, and other crimes; 2) cannabis-impaired driving and related motor-vehicle-crashes; 3) cannabis sourcing by consumers; and 4) cannabis market evolution and dynamics. The data identified were extracted, organized and narratively summarized by topic. The data reviewed suggest that cannabis-related crimes and enforcement have substantially decreased, yet arbitrary (e.g., racialized) enforcement patterns – involving both adults and youths – commonly persist in legalization settings; evidence for ecological effects on other (e.g., property, violent) crimes is mixed. The prevalence of cannabis-impaired driving does appear to be steady or decreasing, while levels of cannabis involved in motor-vehicle-crashes, and overall motor-vehicle-crash fatality levels appear to have increased. In North American legalization settings, the legal sourcing of cannabis has gradually increased to involve 50–70% or more of consumers alongside expanding legal retail market proliferation, while found to be influenced by multiple factors (e.g., product characteristics, price, use intensity). Conversely, legal cannabis sourcing remains much more limited in Uruguay’s restrictive settings. Data on the evolution of illegal cannabis markets is very limited, suggesting some evidence for reductions of illegal production but also shifts or displacement effects (e.g., towards production for or distribution in non-legalization settings), leaving open questions as to the impacts of legalization in these domains. Overall, legalization appears to be meeting some of its socio-legal and specifically crime-reduction goals, yet while key data indicators are mixed or lacking. Focused and expanded research on crime-related outcomes of legalization policies is needed, also given limited benefits to date evidenced for health outcomes.